Studying the effect of ZnO on physical and elastic properties of (ZnO)x(P2O5)1-x glasses using nondestructive ultrasonic method - Matori, Khamirul Amin; Mohd Zaid, Mohd Hafiz; Hock, Jin Quah; Abd. Aziz, Sidek; Abd. Wahab, Zaidan; Mohd Ghazali, Mohd Sabri (Hindawi Publishing Corporation, 2015)
Binary zinc phosphate glass system with composition of (ZnO)x(P2O5)1−x, ( = 0.1, 0.2, 0.3, 0.4, 0.5 and 0.6 mol%) was successfully prepared using a conventional melt-quenching method. Composition dependence of physical properties and elastic properties in the (ZnO)x(P2O5)1−x were discussed in association with the effects of adding zinc oxide (ZnO) as a modifier. The addition of ZnO modifier was expected to produce substantial changes on physical properties of the phosphate glasses. An increase in density values of the phosphate glasses was observed. Elastic moduli were studied by measuring ultrasonic longitudinal and shear velocities ( and ) of the glasses at room. Longitudinal modulus, shear modulus, bulk modulus, Young’s modulus, Poisson’s ratio, and Debye temperature were derived from both data of velocities and respective density of all of the samples. Findings from present work showed dependence of density and elastic moduli of each ZnO-P2O5 series on glass composition.